Perspectives on European Earthquake Engineering and Seismology Volume 1 - Ansal, Atilla (Geotechnical, Geological and Earthquake Engineering, Vol. 34, 2015)
Civil Engineering; Natural Hazards; Geotechnical Engineering & Applied Earth Sciences Industry Sec; 2ECEES; Earthquake Engineering; Performance Based Design and Earthquake Engineering; Irregular Buildings and Earthquakes; Historical Structures and Earthquakes; Precast Buildings and Earthquakes; Bridge Design and Earthquakes